PROBLEMS OF RISK COMMUNICATION: NON-GOVERNMENTAL ORGANIZATIONS AND THEIR ROLE IN THE DEVELOPMENT OF THE PUBLIC OPINION ON ISSUES OF POPULATION’S RADIATION PROTECTION - A. M. Biblin; N. M. Vishnyakova; K. V. Varfolomeeva; S. A. Zelentsova; E. V. Khramtsov; R. R. Akhmatdinov (Радиационная гигиена)
Events connected with the development and improvement of the nuclear industry are usually ambiguously perceived by the public. Mass-media and Internet play a leading role in the development of the public opinion on the most relevant public life issues, ecology and radiation safety in particular. Non-governmental organizations can impact the adequate perception of the issues of the radiation safety in the region by the public. Materials and methods: this study is focused on the primary evaluation of the data on the results of the sociological survey of three regions of the North-West of the Russian Federation: St-Petersburg, Leningrad and Murmansk regions; and the assessment of the websites of the non-governmental organizations, activities of the non-governmental organizations in the Internet and social networks. Results: the study indicated that non-governmental organizations actively use Internet and social networks in their practice. All the relevant non-governmental organizations have websites and social network accounts. Based on the number of the subscribers in social networks, it was possible to mark two non-governmental organizations: Greenpeace and World Wildlife Fund (WWF) with more than 400000 subscribers each. VKontakte social network was assessed as the most effective mean of communicating with the public; a total number of subscribers on the groups of major non-governmental organizations exceeds 500000 persons. These two organizations are the most popular and trusted by the public. Greenpeace is known to 26% of respondents; WWF – to 11%. The population of the Murmansk region is more informed about the actions of the non-governmental organizations. 48% of the respondents in the Murmansk region named at least one non-governmental organization answering the question “What non-governmental organizations active in the field of radiation protection do you know?” with the corresponding 18% and 29% in St-Petersburg and Leningrad region respectively. Nongovernmental organizations have a sufficient potential of influence on the adequate perception of the issues of the radiation protection by the public in the region; however, that potential is not fully implemented. Despite that, activities of the non-governmental organizations should be considered while developing the adequate perception of the radiation factors by the public.